Acquisition of Tidal Measurement Data in The Waters Around Bitung City For Predictional Purposes: Akuisisi Data Pengukuran Pasang Surut di Perairan Sekitar Kota Bitung Untuk Keperluan Prediksi - Wuwung, Vanessa; Rampengan, Royke M.; Manengkey, Hermanto W.K.; Bara, Robert. A.; Djamaaludin, Rignolda; Losung, Fitje (Sam Ratulangi University, 2023)
The existence of the waters around the city of Bitung with all its intensive utilization makes information regarding tidal conditions very important to continue to study. In the waters around Bitung City, there are two tidal measurement stations, the BMKG station, and the IOC station. This research was conducted to analyze the accuracy of tide prediction results based on measurement data at two tide stations located in the waters around Bitung City. The research was conducted by applying the least squares method to calculate the amplitude and phase of the tidal harmonic constants, followed by predicting tidal data. The result was that the most accurate predictions were obtained through a study of tidal data from IOC measurement stations in March–April 2021 with an average deviation of 4.35 cm. However, tide predictions using BMKG measurement station data are more consistent with an average deviation of ± 5 cm, compared to the average deviation of tide predictions from IOC measuring stations which vary from 4.35 – 27.67 cm. Keywords: Tidal prediction, Tidal constants, Tidal amplitude, Mean sea level Abstrak Keberadaan perairan sekitar Kota Bitung dengan semua pemanfaatan intensifnya menyebabkan informasi menyangkut kondisi pasang surut sangat penting untuk terus dikaji. Di perairan sekitar Kota Bitung terdapat dua stasiun pengukuran pasang surut, yaitu stasiun BMKG dan stasiun IOC. Penelitian ini dilakukan dengan tujuan menganalisis akurasi hasil prediksi pasut berdasarkan data hasil pengukuran di dua stasiun pasut yang berlokasi di perairan sekitar Kota Bitung. Penelitian dilakukan dengan menerapkan metode kuadrat terkecil untuk menghitung amplitudo dan fase konstanta harmonik pasang surut, dilanjutkan dengan melakukan prediksi data pasut. Hasilnya diperoleh bahwa prediksi yang paling akurat diperoleh melalui kajian data pasut stasiun pengukuran IOC pada bulan Maret–April 2021 dengan deviasi rata-rata sebesar 4,35 cm. Walaupun demikian prediksi pasut menggunakan data stasiun pengukuran BMKG lebih konsisten dengan deviasi rata-rata ± 5 cm, dibandingkan dengan deviasi rata-rata prediksi pasut stasiun pengukuran IOC yang bervariasi dari 4,35 – 27,67 cm. Kata Kunci : Prediksi pasut, Konstanta pasut, Amplitudo pasut, Duduk tengah muka laut